2017
DOI: 10.1016/j.jclepro.2016.11.159
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of a polymer electrolyte membrane fuel cell system for passenger vehicles

Abstract: In moving towards a more sustainable society, hydrogen fueled polymer electrolyte membrane (PEM) fuel cell technology is seen as a great opportunity to reduce the environmental impact of the transport sector.However, decision makers have the challenge of understanding the real environmental consequences of producing fuel cell vehicles (FCVs) compared to alternative green cars, such as battery electric vehicles (BEVs) and more conventional internal combustion engine vehicles (ICEVs). In this work, we presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 44 publications
3
78
0
1
Order By: Relevance
“…The impact of platinum group metals, although their small amount, lies mainly in their extraction process, as suggested in previous studies [56,57] and confirmed by the impacts flowchart shown in Figure 11.…”
Section: Lca Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The impact of platinum group metals, although their small amount, lies mainly in their extraction process, as suggested in previous studies [56,57] and confirmed by the impacts flowchart shown in Figure 11.…”
Section: Lca Resultssupporting
confidence: 82%
“…The impact of platinum group metals, although their small amount, lies mainly in their extraction process, as suggested in previous studies [56,57] and confirmed by the impacts flowchart shown in Figure 11. As can be seen in Figures 9 and 10, for both hydrogen-based systems, a significant impact is given by the gas tanks (62% for the stationary system and 49% for the mobile one).…”
Section: Lca Resultssupporting
confidence: 82%
“…[4] The requirements that materials should meet in order to be good candidates as H 2 storage and release media can be generally described as follows. For example, a few years ago, the Department of Energy (DOE) in the United States (US) set up the following requirement for hydrogen storage materials for on-board implementation: a material should have a minimum gravimetric hydrogen density of 1.5 kWh kg −1 (4.5 wt% hydrogen, system-based) to be a good candidate as on-board H 2 -storage medium for full-fleet, light-duty vehicles in the US by the year 2020.…”
Section: Materials and Chemical Systems For Hydrogen Storage And Releasementioning
confidence: 99%
“…In the case of sorbent materials, research efforts should continue around the development of highly porous materials with optimized pore size, high pore volume and large specific surface area to achieve the highest possible volumetric and gravimetric hydrogen storage capacities. [4] From a practical point of view, formate/bicarbonate and even FA/formate are more advantageous as energy storage systems than FA/CO 2 , because the spent fuels, i.e., bicarbonate and formate, respectively, are not gases or can exit in solution at ambient condition, and are thus easier to manage. Catalysts that allow the regeneration or reproduction of the chemical hydrides from the spent fuels are also equally needed.…”
Section: Prospective and Outlookmentioning
confidence: 99%
See 1 more Smart Citation